Adoption Of Blockchain Technology In The Financial Sector: Lessons Learned From International Experiences - Cherif, Nour El Houda; Azaizia, Sarra (جامعة الوادي - University of Eloued, 2023)
This study aims to analyze the increasing interest in the adoption of Blockchain technology in the financial sector, as demonstrated by the experiences of countries such as the UAE, Egypt, and Saudi Arabia. These experiences provide valuable insights into the potential benefits and challenges of implementing Blockchain technology in the banking industry. Key lessons learned from these experiences include the importance of collaboration and partnerships in the adoption of Blockchain technology, the need for regulatory clarity and supportive legislative frameworks, and the potential benefits of Blockchain technology in improving the efficiency, transparency, and security of financial transactions.
مقال
Keywords: blochchain ; islamic finance ; financial sector ; fintech